2020
DOI: 10.5194/acp-20-4477-2020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SO<sub>2</sub> on optical properties of secondary organic aerosol generated from photooxidation of toluene under different relative humidity conditions

Abstract: Abstract. Secondary organic aerosol (SOA) has great impacts on air quality, climate change and human health. The composition and physicochemical properties of SOA differ greatly because they form under different atmospheric conditions and from various precursors as well as differing oxidation. In this work, photooxidation experiments of toluene were performed under four conditions (dry, dry with SO2, wet and wet with SO2) to investigate the effect of SO2 under different relative humidities on the composition a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…BrC can be photobleached by oxidations with hydroxyl radical (·OH), ozone (O 3 ), and oxygen (O 2 ) (Schnitzler & Abbatt, 2018; Sumlin et al., 2018), and transformed through photo‐enhancement involving nitrate radical (NO 3 ) and ammonium salt (NH 4 + ) (De Haan et al., 2017; Lee et al., 2013; Li et al., 2020). Sulfur dioxide (SO 2 ) can effectively enhance BrC absorption with the presence of N‐containing precursors under high relative humidity (RH) (Nakayama et al., 2015, 2018; Zhang et al., 2020). Through chamber simulation coupling with chromatographic separation and mass spectrometric detection (MSD), N‐containing aromatic compounds were recognized as vital BrC contributors (Desyaterik et al., 2013; Lin et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…BrC can be photobleached by oxidations with hydroxyl radical (·OH), ozone (O 3 ), and oxygen (O 2 ) (Schnitzler & Abbatt, 2018; Sumlin et al., 2018), and transformed through photo‐enhancement involving nitrate radical (NO 3 ) and ammonium salt (NH 4 + ) (De Haan et al., 2017; Lee et al., 2013; Li et al., 2020). Sulfur dioxide (SO 2 ) can effectively enhance BrC absorption with the presence of N‐containing precursors under high relative humidity (RH) (Nakayama et al., 2015, 2018; Zhang et al., 2020). Through chamber simulation coupling with chromatographic separation and mass spectrometric detection (MSD), N‐containing aromatic compounds were recognized as vital BrC contributors (Desyaterik et al., 2013; Lin et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The oxidants (OH radical, NO x , O 3 , NO 3 radicals) also have a great influence on the chemical reaction processes, attributing to the different chemical composition and RI values of the formed products. For example, Zhang et al 98 conducted experiments with toluene in the presence of SO 2 under different RH conditions and showed that an increase in RH could enhance both the scattering and absorbing properties of SOA. The presence of SO 2 could slightly lower the scattering property of SOA and improve the absorption property of SOA.…”
Section: Impact Of Oxidations On Physicochemical Properties Of Aerosolsmentioning
confidence: 99%
“…The relative humidity (RH) has been highlighted in recent research on the atmospheric environment because it changes with different regions, seasons, and times of day. [23][24][25] The RH effects on the formation processes of aromatic SOA have been investigated in previous studies. 9,25 Due to the formation of hydroxy products from aqueous reactions, a high RH can lead to a much higher SOA yield from the photooxidation of toluene.…”
Section: Introductionmentioning
confidence: 99%